2020
DOI: 10.3390/life10100239
|View full text |Cite
|
Sign up to set email alerts
|

Markers of Endothelial Injury and Dysfunction in Early- and Late-Onset Preeclampsia

Abstract: With regard to differences in the clinical symptoms of preeclampsia (PE), the degree of endothelial dysfunction may differ between early and late-onset preeclampsia (EOP and LOP). The authors of this study examined it by assessing the endothelial injury level in women with EOP (20 patients) and LOP (20 patients) and in normotensive pregnant women (20 patients) in their late second and third trimesters of pregnancy, using the two markers—the serum concentration of hyaluronan (HA) and the serum level of soluble … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
16
1
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 14 publications
(18 citation statements)
references
References 25 publications
0
16
1
1
Order By: Relevance
“…However, some controversies concern the difference in the levels of sVCAM-1 in patients with EOP and LOP. In the earlier study, sVCAM-1 was found to be lower in LOP compared to EOP [39], whereas more recent studies did not show such a difference [11,40]. Moreover, the rs3181092 polymorphism of VCAM-1 was found to be associated with an increased risk of PE [41].…”
Section: Vcam-1mentioning
confidence: 99%
See 2 more Smart Citations
“…However, some controversies concern the difference in the levels of sVCAM-1 in patients with EOP and LOP. In the earlier study, sVCAM-1 was found to be lower in LOP compared to EOP [39], whereas more recent studies did not show such a difference [11,40]. Moreover, the rs3181092 polymorphism of VCAM-1 was found to be associated with an increased risk of PE [41].…”
Section: Vcam-1mentioning
confidence: 99%
“…(1) a predisposition to PE in pregnant women with a primary endothelial dysfunction and (2) a secondary endothelial injury as a consequence of a primary impaired placental perfusion, the two main phenomena in the pathophysiology of PE [9][10][11].…”
Section: Preeclampsia (Pe)mentioning
confidence: 99%
See 1 more Smart Citation
“…The outcome of early-onset is believed to be worse compared to that of late-onset. However, Kornacki's group attempted to compare the difference of the endothelial injury between the early-onset and late-onset preeclampsia [21]. It is interesting to find that there is no statistically significant difference of degree for endothelial injury, using serum concentrations of hyaluronan and serum level of soluble vascular cell adhesion molecule-1 (sVCAM-1) as tools [21].…”
mentioning
confidence: 99%
“…However, Kornacki's group attempted to compare the difference of the endothelial injury between the early-onset and late-onset preeclampsia [21]. It is interesting to find that there is no statistically significant difference of degree for endothelial injury, using serum concentrations of hyaluronan and serum level of soluble vascular cell adhesion molecule-1 (sVCAM-1) as tools [21]. Finally, Vega et al found that women with IgM antibodies against the phosphatidylserine-prothrombin complex (aPS/PT) titers having higher pulse wave velocity (PWV) levels [22].…”
mentioning
confidence: 99%